To Prevent or Promote Grid Expansion? Analyzing the Future Role of Power Transmission in the European Energy System - Cao, Karl-Kiên; Pregger, Thomas; Haas, Jannik; Lens, Hendrik (Frontiers in Energy Research, 2021)
Future energy-supply systems must become more flexible than they are today to accommodate the significant contributions expected from intermittent renewable power sources. Although numerous studies on planning flexibility options have emerged over the last few years, the uncertainties related to model-based studies have left the literature lacking a proper understanding of the investment strategy needed to ensure robust power grid expansion. To address this issue, we focus herein on two important aspects of these uncertainties: The first is the relevance of various social preferences for the use of certain technologies, and the second is how the available approaches affect the flexibility options for power transmission in energy-system models. To address these uncertainties, we analyze a host of scenarios. We use an energy-system optimization model to plan the transition of Europe’s energy system. In addition to interacting with the heating and transport sectors, the model integrates power flows in three different ways: as a transport model, as a direct-current power-flow model, and as a linearized alternating-current power-flow model based on profiles of power transfer distribution factors. The results show that deploying transmission systems contributes significantly to system adequacy. If investments in new power-transmission infrastructure are restricted—for example, because of social opposition—additional power generation and storage technologies are an alternative option to reach the necessary level of adequacy at 2% greater system costs. The share of power transmission in total system costs remains widely stable around 1.5%, even if cost assumptions or the approaches for modeling power flows are varied. Thus, the results indicate the importance of promoting investments in infrastructure projects that support pan-European power transmission. However, a wide range of possibilities exists to put this strategy into practice.